Adverse Events Among Patients With Diabetes and Ambulatory Practice Characteristics: Evidence From a Nationally Representative Survey. (June 2018) - Gabriel, Meghan Hufstader; Atkins, Danielle; Chisholm, Latarsha; Noblin, Alice
Medications are the most common treatment modality for diabetes; however, medications may lead to inadvertent injury. Reducing adverse events in patients with diabetes is an important health care goal. Using pooled data from the 2011-2013 National Ambulatory Medical Care Survey, this cross-sectional, observational study explored univariate associations between patient safety for patients with diabetes as measured by adverse events and practice characteristics, including health information technology capabilities. This study found that the overall rate of adverse events among adults with diabetes is 7%, inclusive of injury, poisoning, or adverse effect of medical/surgical care or medicinal drug. We find evidence that e-prescribing, seeing a primary care provider, and being an established patient are associated with less adverse events.